Association of serum insulin-like growth factor-1 and adrenocorticotropic hormone therapeutic response in patients with infantile epileptic spasms syndrome - Lin, Ka-Na; Han, Feng; Wang, Ying-Yan; Zhao, Wei; Wang, Ji-Wen; Li, Hao; Zhou, Yun-Qing (Frontiers in Pharmacology, 2025)
BackgroundInfantile epileptic spasm syndrome (IESS), a rare age-specific epileptic encephalopathy, exhibits limited therapeutic efficacy, with approximately 50% of patients showing resistance to adrenocorticotropic hormone (ACTH) monotherapy. Herein, we investigated the association between serum insulin-like growth factor-1 (IGF-1), insulin-like growth factor-binding protein-3 (IGFBP-3), their ratio, and short-term ACTH therapeutic response in IESS, alongside their correlation with video-electroencephalogram (VEEG) characteristics.MethodsThis retrospective study included IESS patients who received ACTH treatment at Shanghai Children’s Medical Center from July 2021 to November 2024. Clinical data, including serum IGF-1, IGFBP-3 levels, VEEG findings, and short-term treatment responses, were collected. Before ACTH therapy, we classified patients into hypsarrhythmia and non-hypsarrhythmia groups based on VEEG findings. The hypsarrhythmia cohort was further subdivided into ACTH responders and non-responders. Statistical analyses employed independent t-tests, Mann-Whitney U tests, chi-square tests, and Spearman’s rank correlation.ResultsA total of 21 patients (14 hypsarrhythmia, 7 non-hypsarrhythmia) were enrolled. The hypsarrhythmia population exhibited significantly lower serum IGF-1 levels and IGF-1/IGFBP-3 ratios (p < 0.05) compared to the non-hypsarrhythmia population. Within the hypsarrhythmia population, responders (n = 9) showed higher IGF-1, IGFBP-3 levels, and IGF-1/IGFBP-3 ratios than non-responders (n = 5) before ACTH treatment (p < 0.05). Post-ACTH treatment, serum IGF-1 and IGFBP-3 levels increased in all patients, with greater elevation observed in responders.ConclusionOur findings demonstrate that serum IGF-1, IGFBP-3 levels, and their ratio correlate with both hypsarrhythmia severity and short-term ACTH response in IESS patients. These biomarkers may help guide personalized treatment decisions.